Ekonomska diplomatija Bosne i Hercegovine / Economic Diplomacy of Bosnia and Herzegovina (Pregled: časopis za društvena pitanja / Periodical for social issues, 2020)
Due to its political, legal and social stratification and lack of a single economic market, Bosnia and Herzegovina has poorly developed economic diplomacy in practice. Recently, awareness of the importance of economic diplomacy as a key instrument in international advent has emerged, yet everything remained on theoretical positioning as a high priority of BiH's foreign policy. In developed countries this is indeed the case, because the state institutions support is a crucial element in conquering foreign markets. In today's global economy, not only companies, but also states are active participants in market events, promoting, lobbying and helping their national companies fight for their share of the market cake, with the aim of increasing foreign trade, volume and value of foreign investments, increasing employment, and generally economic growth and overall business climate and national well-being.
Keywords: Economic diplomacy; model of economic diplomacy; institutional bearers; business climate; country image; corruption